The Search for Unlimited Productivity. - Meil, Doug (Communications of the ACM, 2021)
The article discusses the quest to develop computer software with unlimited productivity capabilities. The author examines the various challenges facing computer software development teams and management including prioritization, quality of the code, and the rapidity of the software deployment. The author also discusses the concept of the Inversion of Control pattern.